THE IMAGE OF BABUR IN THE INTERPRETATION OF HAROLD LAMB - Nigmatullayevich, Kamolov Ikhtiyor; Ravshanovna, Khayrullayeva Kamola; Khabibovna, Quvvatova Dilrabo (The journal of contemporary issues in business and government, 2021)
Poet and ruler Z.M. Babur belongs to a number of great figures who made a valuable contribution to world civilization. For this reason, literary and historical works of a world scale are still created about this historical person. These historical and artistic sources describe the difficult but very meaningful life of the great thinker. The article provides a comparative analysis of the novel "Babur the Tiger" by the American orientalist Harold Lamb with such historical sources as the memoirs “Baburname” by Babur and “Tarikhi Rashidiy” by Mirzo Mukhammad Khaidar from the point of view of a biographical approach.